Underwater sound levels in the Canadian Arctic, 2014–2019. (July 2021) - Halliday, William D.; Barclay, David; Barkley, Amanda N.; Cook, Emmanuelle; Dawson, Jackie; Hilliard, R. Casey; Hussey, Nigel E.; Jones, Joshua M.; Juanes, Francis; Marcoux, Marianne; Niemi, Andrea; Nudds, Shannon; et al.
Abstract: The Arctic has been a refuge from anthropogenic underwater noise; however, climate change has caused summer sea ice to diminish, allowing for unprecedented access and the potential for increased underwater noise. Baseline underwater sound levels must be quantified to monitor future changes and manage underwater noise in the Arctic. We analyzed 39 passive acoustic datasets collected throughout the Canadian Arctic from 2014 to 2019 using statistical models to examine spatial and temporal trends in daily mean sound pressure levels (SPL) and quantify environmental and anthropogenic drivers of SPL. SPL (50–1000 Hz) ranged from 70 to 127 dB re 1 μPa (median = 91 dB). SPL increased as wind speed increased, but decreased as both ice concentration and air temperature increased, and SPL increased as the number of ships per day increased. This study provides a baseline for underwater sound levels in the Canadian Arctic and fills many geographic gaps on published underwater sound levels. Highlights: Large gaps exist in our understanding of underwater sound levels across the Arctic. We analyzed 39 acoustic datasets collected in the Canadian Arctic from 2014 to 2019. Wind speed and ice concentration caused large variation in underwater sound levels. Underwater noise from ships was an important source of noise in open water season. Our study fills numerous gaps knowledge on underwater sound levels in the Arctic.